Hope amidst neglect: Mycetoma Research Center, University of Khartoum. A holistic management approach to achieve the United Nations' Sustainable Development Goals. - Ahmed Hassan Fahal; Iman Siddig Ahmed; Ali Awadallah Saaed; Dallas J Smith; Fabiana Alves; Borna Nyaoke; Kingsley Asiedu; Roderick Hay (PLoS Neglected Tropical Diseases)
Mycetoma is a debilitating neglected tropical disease that affects individuals worldwide, particularly in regions where there is poverty and limited health care access. The Mycetoma Research Center (MRC), based in Khartoum, Sudan, provides a sustainable, holistic approach to patient care as the only World Health Organization collaborating center for mycetoma. We describe MRC activities that align with the United Nations' Sustainable Development Goals to control mycetoma in Sudan and globally.